How managers frame capital budgeting in investor communications - Battalio, Robert; Loughran, Tim; McDonald, Bill (Journal of Corporate Finance, 2026)
We create a lexicon of 45 capital budgeting terms and document manager language usage in earnings conference calls during 2010-2020. A sharp contrast between prior survey evidence and capital budgeting terms actually spoken by managers during conference calls is reported. Although surveys suggest that many managers use sensitivity analysis and real options for capital budgeting decisions, these terms almost never occur in any conference calls. Managers of large firms generating more positive financial performance tend to talk more about capital budgeting in earnings calls. Finally, we find that companies that mention payback rather than net present value are smaller in size, have less R&D expenses, and are younger in age.